Effects of Holding Time During Artificial Aging Process on AA6061 to the Mechanical Properties - Atria Pradityana; Erik Kurniawan Widyantoro (IPTEK Journal of Proceedings Series, 2019)
Materials that have been frequently used for automotive or construction equipment are Aluminum Alloys (AA) 6061. Artificial aging is one of the processes to obtain optimal strength and hardness values. In this process, depending on the temperature and holding time. In this study, experiments have been carried out on the effects of holding time during the artificial aging process. Heating a solid solution at 300C for 1 hour is the first step. The holding time variations used are 1, 2, 3, 4, and 5 hours. Experiments have been made on impact strength, hardness values and microstructure. For hardness values decrease with increasing holding time. When holding time for 1 hour has a value of 80.8 HVN while the holding time of 5 hours has a hardness value of 47.4 HVN. But in impact testing, the impact strength increases with increasing holding time. Both of these have been supported by microstructure observation data.